Pelatihan Pembelajaran Praktik Wudhu Dan Sholat Di Tpq An-Nuur Desa Kebonrejo - Solhah; Sofiana Zain (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and skills needed for themselves, the people of the nation and the state. Everyone who will perform the prayers will certainly abide first. Many of us see people with perfunctory or imperfect ablutions. Sometimes there are parts of the ablution members that are not exposed to water. In fact, if they know how great the Islamic sharia about ablution is, they will certainly try to perfect their ablutions. The general purpose of implementing this program is to provide learning and practice of ablution and prayer for the anank-children of TPQ An-Nuur Kebonrejo Village and specifically the purpose of this program is to increase understanding of ablution material and prayers. The research approach used in this study is the PAR or Participatory Action Research method. . This research is one of the research models that seeks something to link the research process into the process of social change. The social change in question is how in the empowerment process can realize three benchmarks, namely the joint commitment with TPQ An-Nuur Kebonrejo Village.TPQ children themselves actually already know how to wudlu and pray, but they still need more guidance so that they can know how wudlu and prayer can be valid.